Librarian's guide to online searching - Bell, Suzanne S. (Santa Barbara, California Libraries Unlimited, 2012)
"This complete guide provides librarians and students at every level of experience with proven strategies and tools for efficient online searching, covering commonly available subject databases and principles of effective searching"--Provided by publisher.
1: Database structure for everyone: Records, fields, and indexes -- 2: The searcher's toolkit: Part 1 -- 3: The searcher's toolkit: Part 2 -- 4: Social science databases -- 5: Databases for science and medicine -- 6: Bibliographic databases -- 7: Humanities databases -- 8: Numerical databases -- 9: Focus on people -- 10: Choosing the right resource for the question -- 11: Evaluating databases -- 12: Teaching other people about databases.
Keywords: Database searching; Electronic information resource searching